How Does Accreditation Fit Into the Picture?. Issue 145 (March 2015) - McDavid, James C.; Huse, Irene
Abstract: Since evaluation does not currently accredit preparation programs, the content of this chapter was virtually a blank slate for the authors. Fittingly, they began by reviewing some background literature as to basic terms, what accreditation might entail, and critically parsing out the benefits of doing so. From there they proceeded to examine fields with a kinship to evaluation (accounting, business management, and human resource development) that have implemented systems to provide accredited status for their educational programs. The results have been questionable and led to perhaps unanticipated recommendations for what evaluation should be considering. © Wiley Periodicals, Inc., and the American Evaluation Association.